Biallelic Mutations in GNB3 Cause a Unique Form of Autosomal-Recessive Congenital Stationary Night Blindness - Vincent, Ajoy; Audo, Isabelle; Tavares, Erika; Maynes, Jason T.; Tumber, Anupreet; Wright, Thomas; Li, Shuning; Michiels, Christelle; Banin, Eyal; Bocquet, Beatrice; De Baere, Elfride; Casteels, Ingele; et al. (American journal of human genetics, 2016)
Congenital stationary night blindness (CSNB) is a heterogeneous group of non-progressive inherited retinal disorders with characteristic electroretinogram (ERG) abnormalities. Riggs and Schubert-Bornschein are subtypes of CSNB and demonstrate distinct ERG features. Riggs CSNB demonstrates selective rod photoreceptor dysfunction and occurs due to mutations in genes encoding proteins involved in rod phototransduction cascade; night blindness is the only symptom and eye examination is otherwise normal. Schubert-Bornschein CSNB is a consequence of impaired signal transmission between the photoreceptors and bipolar cells. Schubert-Bornschein CSNB is subdivided into complete CSNB with an ON bipolar signaling defect and incomplete CSNB with both ON and OFF pathway involvement. Both subtypes are associated with variable degrees of night blindness or photophobia, reduced visual acuity, high myopia, and nystagmus. Whole-exome sequencing of a family screened negative for mutations in genes associated with CSNB identified biallelic mutations in the guanine nucleotide-binding protein subunit beta-3 gene (GNB3). Two siblings were compound heterozygous for a deletion (c.170_172delAGA [p.Lys57del]) and a nonsense mutation (c.1017G>A [p.Trp339∗]). The maternal aunt was homozygous for the nonsense mutation (c.1017G>A [p.Trp339∗]). Mutational analysis of GNB3 in a cohort of 58 subjects with CSNB identified a sporadic case individual with a homozygous GNB3 mutation (c.200C>T [p.Ser67Phe]). GNB3 encodes the β subunit of G protein heterotrimer (Gαβγ) and is known to modulate ON bipolar cell signaling and cone transducin function in mice. Affected human subjects showed an unusual CSNB phenotype with variable degrees of ON bipolar dysfunction and reduced cone sensitivity. This unique retinal disorder with dual anomaly in visual processing expands our knowledge about retinal signaling.